Adrenal solitary fibrous tumor: A case report - Yonli, Diataga Sylvestre (Urol Case Rep, 2019)
Solitary fibrous tumor (SFT) is a rare spindle cell neoplasm, originally described in the pleural cavity. It may also occur in extrapleural organs like adrenal gland. We present a case of a fifty two-year old Arab man who has been admitted in urology department for right lumbar pain. A suspect malignant adrenal mass has been detected. He underwent right adrenalectomy and histologically it was SFT. The follow-up three years after surgery is unremarkable. The prognosis of SFT after surgery is unpredictable. A long term follow-up is mandatory to detect local recurrence or distant metastasis.